Ability to Monitor National Responses to the HIV Epidemic “Beyond Viral Suppression”: Findings From Six European Countries - Safreed-Harmon, Kelly; Kall, Meaghan; Anderson, Jane; Azzopardi-Muscat, Natasha; Behrens, Georg M. N.; d'Arminio Monforte, Antonella; Davidovich, Udi; Noori, Teymur; Lazarus, Jeffrey V. (Frontiers in Public Health, 2020)
Objective: With more PLHIV aging into their 50s and beyond in settings where antiretroviral therapy is widely available, non-AIDS comorbidities and health-related quality of life (HRQoL) are becoming major challenges. Information is needed about whether national HIV monitoring programmes have evolved to reflect the changing focus of HIV care. Methods: We created a 56-item English-language survey to assess whether health systems report on common health-related issues for people with HIV including physical and mental health comorbidities, HRQoL, psychosocial needs and fertility desires. One expert was identified via purposive sampling in each of six countries (Estonia, Italy, the Netherlands, Slovenia, Sweden and Turkey) and was asked to participate in the survey. Results: Three respondents reported that the current monitoring systems in their countries do not monitor any of four specified aspects of ten comorbidities including bone loss, cardiovascular disease and neurocognitive disorders. Two respondents stated that their countries potentially can report on leading causes of hospital admission among PLHIV, and five, leading causes of death. In three countries, respondents reported that there was the ability to report on the HRQoL of PLHIV. In two countries, respondents provided data on the percentage of PLHIV denied health services because of HIV status in the past 12 months. Conclusions: This study identified areas for potential HIV monitoring improvements in six European countries in relation to comorbidities, HRQoL, discrimination within health systems and other issues associated with the changing nature of the HIV epidemic. It also indicated that some countries either currently monitor or have the ability to monitor some of these issues. There are opportunities for health information systems in European countries to expand the scope of their HIV monitoring in order to support decision-making about how the long-term health-related needs of PLHIV can best be met.